Cryptosporidiosis in patients with diarrhea and chronic liver diseases - Nasser Mousa; Ahmed Abdel-Razik; Hala El-Nahas; Atef El-Shazly; Mohammad Abdelaziz; Marwa Nabih; Magdy Hamed; Mohammad Eissa; Narmin Effat; Walled Eldars (Journal of Infection in Developing Countries)
Introduction: The aim of this study was to evaluate the epidemiology and clinical significance of Cryptosporidium in patients with diarrhea and chronic liver diseases. Methodology: The study included 150 patients with chronic liver diseases and diarrhea, and 50 subjects with diarrhea as a control group. Stool samples were screened for the presence of Cryptosporidium by microscopic examination after modified Ziehl-Neelsen staining and detection of Cryptosporidium coproantigen by enzyme-linked immunosorbent assay (ELISA). Results: The prevalence of Cryptosporidium infection in patients with chronic liver diseases was 30% (45/150) versus 14% (7/50) in controls. Cryptosporidium infection increased with the progression of chronic liver diseases from Child-Pugh class A to Child-Pugh class C (p<  0.001) and from model for end-stage liver disease (MELD) score ≤ 9 to MELD score > 9 (p< 0.031). Nine patients in Child-Pugh class C with diarrhea associated with Cryptosporidium infection developed hepatic encephalopathy, and only diarrhea was identified as a precipitating factor for hepatic encephalopathy. Conclusions: Cryptosporidium is one of the important causes of diarrhea in patients with chronic liver diseases. The infection significantly increased with the progression of chronic liver diseases. In patients with advanced chronic liver diseases, Cryptosporidium infection may be a precipitating factor of hepatic encephalopathy.